Out of Crisis: Maintaining Hegemony through Rambu Solo Ritual in Toraja - Handayani, Rivi; Ahimsa-Putra, Heddy Shri; Budiman, Christian (Komunitas, 2020)
Rambu Solo ritual has been an inseparable part of the Toraja people for hundreds of years. Nevertheless, this luxurious funeral ritual had experienced various organic crises as new social forces emerged. Using ethnographic methods, this paper attempts to explore how traditional leaders of Toraja maintain the existence of this ritual. Using Gramsci’s theory of hegemony, this article argues that their efforts were carried out in three phases. Firstly, political awareness phase, namely as aristocrat elites, they legitimized the feudal and religious authority of Aluk Todolo belief system that supported the Rambu Solo ritual through modern political strategies; secondly, the phase of solidarity of interests which carried out by negotiating and building commitment with social forces opposing the Rambu Solo ritual; and third, the phase of reaching consensus from the subaltern group is done by involving them in the Pasilaga Tedong betting, one of a series of Rambu Solo rituals where they see it as a medium to show empathy for grieving families rather than betting.